Liminal Masculinity: Narratives of Class and Sexuality in Post-authoritarian Indonesia. (4th May 2019) - Hegarty, Benjamin
ABSTRACT: In contemporary Indonesia, the fragmentation of a collectively-imagined future has generated ambivalent and contradictory ways of being and becoming a man. This article investigates this tension by drawing on interviews and ethnographic data collected from young men aged 18–30 who engage in transactional sex work in the capital city Jakarta. The narratives of these young men suggest that transactional sex is a choice linked to the cultivation of an appropriate form of masculinity. This understanding, however, is complicated by mobility in two ways. First, geographical mobility tied to migration is understood to be necessary to becoming a man who is independent from family. Second, temporal mobility involves future aspirations to marry a woman and become a father, a powerful template for joining middle-class society. Young men find the intersection of geographical and temporal mobility as a source of open-ended liminality in the midst of acute economic precarity and perpetually flexible employment. Serving as narrative accounts of the plasticity of the most widely-held assumptions about the immutable nature of gender, liminal masculinity helps to illuminate the ambiguous effects of global economic forces on forms of moral self-cultivation.